Peran Kesadaran Merek Dalam Memediasi Pengaruh Kredibilitas Celebrity Endorser Terhadap Niat Beli (Studi Pada E-commerce Blibli di Kota Jakarta Selatan) - Akilah Keilani; Osly Usman (Jurnal Ilmiah Wahana Pendidikan, 2026)
The rapid evolution of digital technology and internet infrastructure has fundamentally restructured the global economic paradigm, triggering a massive shift in consumer behavior toward digital commerce. This empirical study aims to comprehensively analyze and describe the mediating role of brand awareness in the complex relationship between celebrity endorser credibility and purchase intention, with a particular focus on the e-commerce platform Blibli. This research is geographically concentrated in South Jakarta, a major urban center in Indonesia characterized by very high digital literacy, strong purchasing power, and an internet penetration rate exceeding 85.87%. Using the South Korean international pop group NCT 127 as the celebrity endorser context, this study investigates how the credibility of global figures influences the cognitive and behavioral responses of potential consumers. Using a quantitative explanatory design with a correlational approach, primary data were collected from 120 respondents in South Jakarta through purposive sampling. The data were evaluated through rigorous statistical tests, including Path Analysis, the Sobel Test for mediation significance, and the Variance Accounted For (VAF) assessment. Structural equation modeling revealed that celebrity endorser credibility had a highly positive and statistically significant direct impact on brand awareness and purchase intention. Furthermore, brand awareness acted as a significant catalyst for purchase intention. Crucially, mediation analysis confirmed that brand awareness exerted a complementary partial mediation effect between endorser credibility and purchase intention. These findings provide profound second-order insights into consumer psychology, suggesting that while credible celebrity figures can directly stimulate transactional desire through parasocial relationships and the trust heuristic, their commercial effectiveness is only substantially amplified and sustained when they successfully embed the brand into consumers' top-of-mind cognitive schemas. This study provides a strategic imperative for e-commerce executives to leverage celebrity endorsements not merely as a short-term vanity metric, but as a fundamental instrument for cultivating long-term brand equity in a hyper-competitive digital ecosystem.